The role and ontogeny of maps in long-distance animal navigation - Morford, J (2023)
Impressive feats of long-distance animal navigation raise questions relating to the proximate causes of such behaviours: what mechanisms facilitate long-distance animal navigation? What is the ontogeny of such behaviours? I focus on how animals determine their position in relation to their goals to determine goalward directions in the first step (the map step) of a two-step navigational process termed map and compass navigation.